Internalisasi Profil Pelajar Pancasila Melalui Pembelajaran Seni dan Budaya di Sekolah Dasar - Nur Kurniasih; Wakhudin Wakhudin (Medan Resource Center, 2023)
This study aims to describe the process of internalizing the Pancasila Student Profile through learning Arts and Culture at SD Negeri 2 Bukateja, Purbalingga, Central Java. This research uses a descriptive qualitative approach with a case study method. The subjects of the study were principals, teachers of grade IV and students of grade IV. Data collection techniques use observation, interviews, and documentation studies. Test the validity of the data in this study using credibility tests, and triangulation of both source triangulation and triangulation techniques. Data analysis techniques use data reduction, data presentation, and conclusions. The results showed that the implementation of internalization uses three stages, namely the stage of value transformation, value transactions, and transinternalization of Pancasila Student Profile values through art and culture learning. This implementation is carried out as a form of efforts to prevent the impact of globalization and achieve one of the school's missions and goals, namely the realization of students who love Indonesian culture and have character in accordance with the values of Pancasila.